Connectivity and vagility determine spatial richness gradients and diversification of freshwater fish in North America and Europe - Griffiths, David (Biological journal of the Linnean Society, 2015)
The latitudinal species richness gradient (LRG) has been the subject of intense interest and many hypotheses but much less consideration has been given to longitudinal richness differences. The effect of postglacial dispersal, determined by connectivity and vagility, on richness was evaluated for the species‐poor European and North American Pacific and species‐rich Atlantic regional freshwater fish faunas. The numbers of species, by habitat, migration and distributional range categories, were determined from regional species lists for these three realms. The current orientation and past connections of drainage channels indicate that connectivity is greatest in the Atlantic and least in the Pacific. With increasing connectivity across realms, endemism decreased and postglacial recolonization increased, as did the LRG slope, with the greatest richness difference occurring between southern Atlantic and Pacific regions. Recolonizing species tended to be migratory, habitat generalists and from families of marine origin. Diversification, as indicated by species/genus ratios, probability of diversification, taxonomic distinctness and endemicity, declined with increasing latitude in all realms and was least in Europe. Richness patterns are consistent with an LRG driven by the time available for postglacial recolonization and by differences in dispersal ability, with richness differences across realms reflecting differences in dispersal and diversification.